IMPACT OF BODY WEIGHT SUPPORTED BACKWARD TREADMILL TRAINING ON WALKING SPEED IN CHILDREN WITH SPASTIC DIPLEGIA - Hamada El Sayed Abd Allah Ayoub (International Journal of Physiotherapy, 2016)
Background: A lot of the ambulating children with spastic diplegia were able to walk with flexed hips, knees and ankles this gait pattern is known as crouch gait. The most needed functional achievement of diplegic children habilitation is to be able to walk appropriately. The development of an independent and efficient walking is one of the main objectives for children with cerebral palsy especially those with spastic diplegia. Method: Twenty children with spastic diplegia enrolled in this study, they were classified into two groups of equal number, eligibility to our study were ages ranged from seven to ten years, were able to ambulate, They had gait problems and abnormal gait kinematics. The control group (A) received selected physical therapy program based on neurodevelopmental approach for such cases, while the study group (B) received partial body weight supported backward treadmill training in addition to regular exercise program. Gait pattern was assessed using the Biodex Gait Trainer II for each group pre and post three months of the treatment program. Results: There was statistically significant improvement in walking speed in the study group (P<0.05) with significant difference when comparing post treatment results between groups (p<0.05). Conclusion: These findings suggested that partial body weight supported backward treadmill training can be included as a supplementary therapeutic modality to improve walking speed and functional abilities of children with diplegic cerebral palsy.